2019
DOI: 10.1016/j.humpath.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Gastric hepatoid adenocarcinomas are a genetically heterogenous group; most tumors show chromosomal instability, but MSI tumors do exist

Abstract: The Cancer Genome Atlas Research Network classified gastric adenocarcinoma into four molecular subtypes: (1) Epstein-Barr virus-positive (EBV), (2) microsatellite-instable (MSI), (3) chromosomal instable (CIN), and (4) genomically stable (GS). The molecular subtypes of gastric hepatoid adenocarcinomas are still largely unknown. We analyzed 52 hepatoid adenocarcinomas for the expression of surrogate markers of molecular subtypes (MLH1, p53, and EBER in situ hybridization) and some biomarkers (p21, p16, Rb, cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
2
19
1
Order By: Relevance
“… 4 , 25 , 26 The mean (SD) age in our sample of 315 patients with HAS was 61.9 (10.2) years, the male to female ratio was approximately 3:1, gastric antrum tumors accounted for 37.1% of cases, and 81.6% of patients had lymph node metastases, consistent with previous reports. 4 , 25 , 26 In addition, to our knowledge, this study was the first to compare the clinicopathological characteristics of patients with simple vs mixed HAS, finding that the 2 groups had similarities in most clinicopathological characteristics; however, patients with simple HAS had higher preoperative serum AFP levels and a higher rate of liver metastasis compared with those with mixed HAS. These findings suggest that monitoring of serum AFP levels and the performance of liver imaging may be more important for patients with simple HAS.…”
Section: Discussionsupporting
confidence: 89%
“… 4 , 25 , 26 The mean (SD) age in our sample of 315 patients with HAS was 61.9 (10.2) years, the male to female ratio was approximately 3:1, gastric antrum tumors accounted for 37.1% of cases, and 81.6% of patients had lymph node metastases, consistent with previous reports. 4 , 25 , 26 In addition, to our knowledge, this study was the first to compare the clinicopathological characteristics of patients with simple vs mixed HAS, finding that the 2 groups had similarities in most clinicopathological characteristics; however, patients with simple HAS had higher preoperative serum AFP levels and a higher rate of liver metastasis compared with those with mixed HAS. These findings suggest that monitoring of serum AFP levels and the performance of liver imaging may be more important for patients with simple HAS.…”
Section: Discussionsupporting
confidence: 89%
“…The major genotypes of gastric malignancy have been defined by The Cancer Genome Atlas (TCGA) Research Network as Epstein-Barr virus-positive (EBV), microsatellite-instable (MSI), genomically stable tumors (GS), and chromosomally instability tumors (CIN): HAS is excluded from any of these due to its scarcity and characteristics of geographical distribution (28). Nevertheless, HASs are genetically heterogeneous groups with a majority of HAC are "CIN" and a small number of HAC with "MSI" (29,30). It has been speculated that HAS is the result of trans-differentiation, transitioning from the intestinal type to hepatoid phenotypic (31); and the emergence of Alpha-fetoprotein (AFP) leading to hepatoid focus in gastric adenocarcinoma, may as a result of dedifferentiation of cancer cells into HAC progenitor cells.…”
Section: Pathogenesismentioning
confidence: 99%
“…Though LIN28 is not as sensitive as SALL4, it is a particular marker (98% specificity) for distinguishing classic HAS from HCCs when combining with SALL4. Other IHC stains for HAS, such as Her-2, alpha 1-antitrypsin (AAT), and alpha 1-antichymotrypsin (ACT), have been reported to be promising in making the diagnosis (30,41).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Cyclin D1 is a regulator of the CDK4/6 enzymes that promote cell cycle progression. Its expression is often increased in malignant tumors and its function is to promote the G1 to S transition of the cell cycle 22,[24][25][26] . The present study indicated that the expression levels of Ki67 and cyclin D1 in cancer tissues were higher than those in normal tissues, suggesting that the proliferative activity of gastric cancer cells was higher than that of normal gastric mucosal cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, only the expression levels of cyclin D1 in EBV-positive gastric cancer and EBV-negative gastric cancer exhibited signi cant differences, suggesting that cyclin D1 was closely associated with EBV-positive gastric cancer and that the EBV virus may affect the expression of this protein in gastric cancer cells. Previous studies have reported that the p16 protein and the latent protein encoded by EBV may affect the expression of cyclin D1 in EBV positive gastric cancer 22,[24][25][26] .…”
Section: Discussionmentioning
confidence: 99%